Midwifery Care for Postpartum Mothers and Breastfeeding for Mrs. N In Dealing With Breast Milk is not yet Smooth - Wilda Nudelis; Diah Atmarina Yuliani (Proceedings Series on Health & Medical Sciences, 2021)
The postpartum period starts from 2 hours after the birth of the placenta until 6 weeks (42 days) after that. Puerperium is a period of recovery, starting from the completion of labor until the uterine devices return to their original state as before pregnancy. Katuk leaves contain compounds that can stimulate the hormone prolactin so that breast milk increases. One of the efforts to increase breast milk is to improve the quality of foods that have a direct effect on milk production, such as green vegetables, katuk leaves, sweet potato leaves, papaya leaves and so on. Katuk leaves contain almost 7% protein and 19% crude fiber, vitamin K, pro-vitamin A (beta-carotene, vitamins B and C. The minerals contained are calcium (2.8%) iron, potassium, phosphorus and magnesium. To find out the application of consuming katuk leaves can launch Mother's Milk. This scientific paper uses a method, namely a case study report using a descriptive method, the location at the residence of Mrs. N Gintung Agung Village, Lambur RT 03 RW 01 Kec. Mrebet Purbalingga Regency. The subject of the case study was the 5th day postpartum mother, namely Mrs. N with a little milk. The case study time is on March 23, 2021. Data collection techniques include interviews and secondary studies including documentation and literature studies. Mother's general condition was good, after consuming katuk leaves, Mother's Milk (ASI) increased. Giving katuk leaves is effective to increase breast milk for nursing mothers.